Key consensus factors as a tool for project-oriented marketing organizations - Olivier MESLY; Christophe Réthoré (Revue Internationale de Psychosociologie et de Gestion des Comportements Organisationnels, 2021)
This article presents Key Consensus Factors (KCFs), i.e., those factors that contribute to mutual trust and effective cooperation among stakeholders in project-oriented marketing organizations (POMOs) that aspire to work together toward success. We extract tentative KCFs using the data percolation methodology, which emphasizes the findings of contrasting cases through research. The results of the 18 semi-structured interviews and two focus groups conducted over four years in two different cultures France and Canada lead us to propose four Key Consensus Factors (KCFs): (1) the establishment of behavioral norms, including mutual listening; (2) the meticulous respect for the triple constraint of the calendar of tasks and activities, costs, and quality; (3) the establishment of a common belief system with a clear goal in mind; and 4) the careful anticipation of unexpected risks. Our paper contributes empirically to discussions about the makeup of KCFs, a topic that has been little addressed in the marketing and project management literature. This paper fills the current gap that exists between the notions of Key Success Factors (KSFs), Key Failure Factors (KFFs) and Key Conensus Factors (KCFs). While countless studies have been conducted on KSFs and KFFs, especially in the project management literature, the literature on KCFs is scarce and, to our knowledge, no research centers on the link between the three sets of factors. Our paper can benefit organizations that engage in significant marketing efforts to carry out projects, as it offers a practical model that can guide their activities toward fruitful relationships among all stakeholders, including with their staff and clients. To that effect, we provide a KCF-based checklist aimed at cohesiveness within project-oriented marketing organizations.